Analisis Kualitatif BKO Deksametason pada Jamu Peningkat Selera Makan dengan Spektrofotometer FTIR - Jelly Syahfitri; Suprianto (Yayasan Penelitian dan Inovasi Sumatera, 2024)
Background: Jamu, a traditional health service deeply ingrained in Indonesian culture, has been utilized for generations. Among the herbal remedies sought after by the public, herbal medicine aimed at enhancing appetite stands out. Unfortunately, the robust demand for these products is often exploited by manufacturers who incorporate pharmaceutical additives. Dexamethasone, a synthetic glucocorticoid renowned for its anti-inflammatory and immunosuppressant attributes, is frequently amalgamated with herbs to stimulate appetite. Its inclusion is prompted by its known side effect of moon face and its potential to enhance appetite with prolonged use. Objective: This research endeavors to ascertain the presence of dexamethasone in the herbal appetite stimulants available in the market within Lubuk Pakam District, Deli Serdang, North Sumatra. Method: Qualitative analysis of dexamethasone was conducted utilizing Fourier Transform Infra Red (FTIR) spectrophotometry. Results: The investigation revealed that several samples of appetite-enhancing herbal medicine suspected to contain dexamethasone indeed exhibited spectra akin to the standard comparison of dexamethasone. Conclusion: Among the ten samples of herbal appetite stimulants scrutinized, eight were found to contain dexamethasone, as evidenced by the congruence of their spectra and functional groups with the comparison standard for dexamethasone.